2021
DOI: 10.1371/journal.pone.0252506
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and inter-trait relationship of tropical extra-early maturing quality protein maize inbred lines under low soil nitrogen stress

Abstract: Information on the genetic diversity, population structure, and trait associations of germplasm resources is crucial for predicting hybrid performance. The objective of this study was to dissect the genetic diversity and population structure of extra-early yellow and orange quality protein maize (QPM) inbred lines and identify secondary traits for indirect selection for enhanced grain yield under low-soil nitrogen (LN). One hundred and ten inbred lines were assessed under LN (30 kg ha -1) and assayed for trypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
0
11
2
Order By: Relevance
“…The average gene diversity of 0.37 observed in this study was higher than the 0.25 reported by Dao et al [ 16 ], but lower than the 0.39 reported by Yang et al [ 17 ]. The PIC value of 0.30 obtained in this study was also higher than the 0.28 and 0.29 reported by Zhang et al [ 18 ] and Abu et al [ 10 ], respectively. The DArTag marker-based clustering of the PVA enriched maize inbred lines was different from the PVA and yield-based grouping of the inbred lines.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The average gene diversity of 0.37 observed in this study was higher than the 0.25 reported by Dao et al [ 16 ], but lower than the 0.39 reported by Yang et al [ 17 ]. The PIC value of 0.30 obtained in this study was also higher than the 0.28 and 0.29 reported by Zhang et al [ 18 ] and Abu et al [ 10 ], respectively. The DArTag marker-based clustering of the PVA enriched maize inbred lines was different from the PVA and yield-based grouping of the inbred lines.…”
Section: Discussioncontrasting
confidence: 73%
“…Genetic distance-based heterotic grouping using simple sequence repeat (SSR) markers have also been effective for increased performance under drought and optimal conditions [ 9 ]. In a recent study, Abu et al [ 10 ] obtained five clusters using single nucleotide polymorphism (SNP) markers for tropical maize inbred lines and predicted high levels of heterosis in crosses involving parents from these clusters.…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies looking at the effect of reduced N level on grain quality have used significantly higher levels of N than is relevant to smallholder farmers in SSA. Under low nitrogen stress in SSA environments, previous maize grain quality assessment studies, such as Abu et al ( 2021 ), Ngaboyisonga and Njoroge ( 2014 ), and (Oikeh et al 1998 ), used N rates ranging from 30 to 120 kg ha −1 . Such application rates are higher than the average N application rates (which is between 12 and 16 kg ha −1 (Heffer and Prud’homme 2015 ; Sheahan et al 2014 ) in smallholder agriculture in SSA.…”
Section: Introductionmentioning
confidence: 99%
“…Naggar et al [81] reported that such high variability suggested that the germplasm was adapted to a wide range of environmental conditions. As reported by Abu et al [82], the wide genetic variability observed suggested that the inbred lines could be important sources of beneficial alleles for low nitrogen breeding programs in sub-Saharan Africa. However, in order to release inbred lines, sources of tolerance have to be identified among adapted populations, and Algerian maize has a wide adaptability to temperate regions and a high degree of genetic diversity and could provide valuable alleles for maize improvement in temperate environments [63,67].…”
Section: Discussionmentioning
confidence: 62%